Application of Discovery Learning Models To Improve Conceptual Mastery of Newton Force And Law - Faradhillah, Faradhillah; Marhami, Marhami; Hadiya, Izkar (UIN Fatmawati Sukarno Bengkulu, 2021)
This study aims to determine the increase in students' mastery of concepts in Newton's Force and Lawmaterial by applying the Discovery Learning model to 10th grade students of Public Vocational School 1Bireuen. The research used was quasi-experimental research with Pretest-Posttest Group Design. Datawas collected in 10th grade TKRO (Automotive Light Vehicle Engineering) as an experimental class with38 students and 10th grade TBSM (Motorcycle Business Engineering) as a control class with 38 students.Data obtained from the results of this study using SPSS for Windows Version 18. Based on the results ofdata analysis to see the results of mastery of students' concepts obtained an average value of 85.16 and thecontrol class average value of 79.95. Data obtained from the test results are used to test the researchhypothesis using the Independent Sample T-test and N-Gain test. From the results of the analysisobtained from the results of the Independent Sample T-test results of the initial and final test valuesobtained tcount> ttable is 3.901> 1.992 with sig (2-tailed) of 0.00 lower than 0.05. The N-Gain value in theexperimental class was 42.24%. Whereas the control class was 38.96%. The results of the analysis ofstudent responses using the Discovery Learning model obtained the percentage of strongly disagreeing at8.2%, disagreeing at 12.3%, agreeing at 48.1%, and strongly agreeing at 31.2%. Based on the results of thestudy it can be concluded that with the Discovery Learning model the mastery of students' conceptmastery especially on Newton's Force and Law material is more improved than using conventionallearning models